One- and two-dimensional search of an equation of state using a newly released 2DRoptimize package. (May 2018) - Jamal, M.; Reshak, A.H.
Abstract: A new package called 2DRoptimize has been released for performing two-dimensional searches of the equation of state (EOS) for rhombohedral, tetragonal, and hexagonal compounds. The package is compatible and available with the WIEN2k package. The 2DRoptimize package performs a convenient volume andc/a structure optimization. First, the package finds the best value forc/a and the associated energy for each volume. In the second step, it calculates the EoS. The package then finds the equation of thec/a ratio vs. volume to calculate thec/a ratio at the optimized volume. In the last stage, by using the optimized volume andc/a ratio, the 2DRoptimize package calculatesa andc lattice constants for tetragonal and hexagonal compounds, as well as thea lattice constant with theα angle for rhombohedral compounds. We tested our new package based on several hexagonal, tetragonal, and rhombohedral structures, and the 2D search results for the EOS showed that this method is more accurate than 1D search. Our results agreed very well with the experimental data and they were better than previous theoretical calculations. Highlights: New 2DRoptimize package for two-dimensional search of the equation of state (EOS). The package is compatible and available with the WIEN2k package. The 2DRoptimize package performs a convenient volume andc/a structure optimization. The 2D search of EOS yielded better accuracy than the 1D search of EOS.